Analisis SWOT dalam Menentukan Strategi Penerapan Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi - Utami, Yuanita; Khairi, Halilul; Sartika, Ika (UI Scholars Hub, 2024)
The implementation of the Integrated Dynamic Archival Information System (SRIKANDI) is an effort to improve government administration services. In its implementation, there are government agencies that are resistant to implementing this application. This has an impact on not achieving the set targets. The research question is what is the SWOT analysis of the implementation of SRIKANDI in government agencies and what is the strategy for the results of this analysis. The aim of the research is to find out ANRI's strategy in achieving the target of implementing SRIKANDI. These strategic steps were analyzed using SWOT analysis (Strength, Weakness, Opportunity and Threats). This research uses descriptive research methods with a qualitative approach. Researchers collect data through the use of secondary data and literature reviews regarding service functions, policy implementation and digital governance. The results of this research indicate that the implementation of the SRIKANDI application needs to be optimized with SO (Strength-Opportunity), WO (Weakness-Opportunity), ST (Strength-Threats), and WT (Weakness-Threats) strategies.